Non-surgical treatment of peri-implantitis with and without erythritol air-polishing a 12-month randomized controlled trial - Armin Selimović; Dagmar F. Bunæs; Stein Atle Lie; Målfrid Aa. Lobekk; Knut N. Leknes (BMC, 2023)
Abstract Background A variety of interventions have been explored in the non-surgical management of peri-implantitis. In spite of extensive testing of various study protocols, effective treatments largely remain unavailable. The objective of the present 12-month single-centre, examiner-masked, randomized controlled clinical trial was to explore whether a low-abrasive erythritol air-polishing system produces added clinical benefit when used adjunctive to conventional non-surgical management of peri-implantitis and to record any associated patient-centered outcomes. Methods Forty-three patients with mild to severe peri-implantitis including at least one implant either received ultrasonic/curette subgingival instrumentation and erythritol air-polishing (test) or ultrasonic/curette instrumentation only (control) at baseline and at 3, 6, 9, and 12 months. Probing depth (PD), bleeding on probing (BoP), dental plaque, suppuration (SUP), crestal bone level (CBL), and peri-implant crevicular fluid (PCF) were recorded at baseline, 6 and 12 months. Visual Analogue Scale (VAS) scores were collected immediately following subgingival interventions at all time-points. Results A reduction in PD was observed from baseline to 6 months for the test (p = 0.006) and control (p < 0.001) and from baseline to 12 months for the control (p < 0.001). No intergroup differences were observed for primary outcome variables PD or CBL over time (p > 0.05). At 6 months, a intergroup difference in PCF was observed in favor of the test (p = 0.042). Moreover, a reduction in SUP from baseline to 6 and 12 months was observed in the test (p = 0.019). Overall, patients in the control group experienced less pain/discomfort compared with the test (p < 0.05), females reporting more pain/discomfort than males (p = 0.005). Conclusions This study confirms that conventional non-surgical management of peri-implantitis produces limited clinical improvement. It is shown that an erythritol air-polishing system may not produce added clinical benefits when used adjunctive to conventional non-surgical management. In other words, neither approach effectively resolved peri-implantitis. Moreover, the erythritol air-polishing system produced added pain/discomfort particularly in female patients. Trial registration The clinical trial was prospectively registered in ClinicalTrials.gov with registration NCT04152668 (05/11/2019).